Advancing the Logic of Polymer Synthesis via Skeletal Rearrangements - Zhukhovitskiy, Aleksandr V.; Ratushnyy, Maxim; Ditzler, Rachael A. J. (Synlett, 2022)
Polymers are ubiquitous materials that have driven technological innovation since the middle of the 20th century. As such, the logic that guides polymer synthesis merit considerable attention. Thus far, this logic has often been ‘forward-synthetic’, which constrains the accessible structures of polymer materials. In this article, we emphasize the benefits of ‘retrosynthetic’ logic and posit that the development of skeletal rearrangements of polymer backbones is central to the realization of this logic. To illustrate this point, we discuss two recent examples from our laboratory – Brook and Ireland–Claisen rearrangements of polymer backbones – and contextualize them in prior reports of sigmatropic rearrangements and skeletal rearrangements of polymers. We envision that further development of skeletal rearrangements of polymers will enable advances in not only the chemistry of such rearrangements and the logic of polymer synthesis, but also polymer re- and upcycling.
Keywords: rearrangement; skeletal editing; polymers; sigmatropic; Brook; Ireland–Claisen; retrosynthetic analysis